Lungworm seroprevalence in free-ranging harbour seals and molecular characterisation of marine mammal MSP. Issue 1 (April 2016) - Ulrich, Sophia Arlena; Lehnert, Kristina; Rubio-Garcia, Ana; Sanchez-Contreras, Guillermo J.; Strube, Christina; Siebert, Ursula
Abstract: Harbour seals ( Phoca vitulina ) are frequently infected with the lungworms Otostrongylus circumlitus and Parafilaroides gymnurus . The infection is often accompanied by secondary bacterial infections and can cause severe bronchopneumonia and even death in affected animals. Hitherto, the detection of lungworm infections was based on post mortem investigations from animals collected within stranding networks and a valid detection method for live free-ranging harbour seals was not available. Recently, an ELISA was developed for detecting lungworm antibodies in harbour seal serum, using major sperm protein (MSP) of the bovine lungworm, Dictyocaulus viviparus as recombinant diagnostic antigen. To determine lungworm seroprevalence in free-ranging harbour seals, serum was taken from four different seal age groups (n = 313) resulting in an overall prevalence of 17.9% (18.9% of males, 16.7% of females). 0.7% of harbour seals up to six weeks of age were seropositive, as were 89% of seals between six weeks and six months, 53.6% between six and 18 months and 24.2% of seals over 18 months of age. In the 18 months and over age group, seropositive animals showed statistically significant reductions in body weight (P = 0.003) and length (P < 0.001). Sera from lungworm infected harbour seals in rehabilitation (n = 6) revealed that duration of antibody persistence may be similar to that of lungworm infected cattle, but further studies are needed to confirm this. Phylogenetic analyses of MSP sequences of different marine and terrestrial mammal parasitic nematodes revealed that lungworm MSP of the genus Dictyocaulus (superfamily Trichostrongyloidea) is more closely related to metastrongylid marine mammal lungworms than to trichostrongylid nematodes of terrestrial hosts. Graphical abstract: Highlights: First study on lungworm seroprevalence in live free-ranging harbour seals. Total seroprevalence was 17.9%, but age-dependent differences were observed. Six weeks to six months old seals showed highest prevalences (89% positives). Seropositive adult seals showed significantly reduced body weight and length. Phylogenetic tree construction using MSP of marine and terrestrial mammal parasites.